Design of Horizontal Shading Devices for Baghdad city’s - Saleem, Younis Mahmoud (Iraqi Journal of Architecture and Planning, 2018)
The use of sun control and shading devices is an important aspect of many energy-efficient building design strategies, where the shading of the building is the first step in the passive cooling systems in buildings. So the starting point of cooling systems is to reduce the solar heat gain by prevent solar radiation from entering the building in the hot period in the same time allow the daylight and benefit from achieving passive heating in cold period. This research interested with design of horizontal shading devices for buildings in Baghdad city. The research problem identified as the need to study the factors influence in deign horizontal shading devices and determining their dimensions. The research aimed to study the horizontal shading device in simple method because this device is the most effective and most commonly used among other types of shading devices. The research analyses the local affecting variables comprising the outside air temperature and intensity of solar radiation during the warm and cold months in Baghdad city. The study prepared for architectural designer the suitable values of extending the shading devices according to orientation, as well as the predictability of the design efficiency of all size of shading devices placed over the windows. The method of this research applied of design horizontal sun breakers with windows in different orientation, which showed the space of flexibility and possibilities in the design of shading devices. The research reach a number of conclusions presented as guideline to assist the designers in making decisions about the use of horizontal shading devices in different design cases.